ANALISIS PENGARUH KEKENTALAN FLUIDA AIR DAN MINYAK KELAPA PADA PERFORMANSI POMPA SENTRIFUGAL - Arijanto Arijanto; Eflita Yohana; Franklin T.H. Sinaga (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2015)
The current industrial world requires equipment, that working effectively and efficiently to reduce operational costs. One tool that is often encountered is the pump. This is because the pumping system is responsible for nearly 20% of the world's electrical energy demand and energy use in industrial plants. One of the most frequent problems encountered in the process of pumping is the viscosity of the fluid. This research aimed to analyze the effect of viscosity of the flow capacity, pump head, power and efficiency of the pump for pump fluid flow of water and coconut oil. Water density 996 kg/m3, oil density of 858 kg/m3, water viscosity of 0.82 mPas, the viscosity of the coconut oil 3,98 mPas. Variations that give the full aperture or100%, opening 75%, 50% and aperture openings 25%. research data calculated from the pressure, rpm, flow, and flow velocity. From the data we receive a pump head, the pump shaft and the efficiency of the performance curve obtained with the method of dimensionless. The research results show the water fluid maximum flow rate is 36 l/min, while the fluid coconut oil is 17 l/min. Value of water fluid head is 15.18 m, while the oil fluid obtained 9.18 m. The value of BHP water fluid 130.04 W, where as the oil fluid is 131.98 W. And for the value of water fluid efficiency 68.46%, while the oil fluid is 16,59%. The conclusion is the value of higher water discharge fluid from the fluid coconut oil, water fluid water head value is higher than the fluid coconut oil, water fluid efficiency values higher than coconut oil, while the value of fluid power pumps oil is higher than the fluid water.